Journal of Computational and Graphical Statistics. (13th June 2014) - Levine, Richard A.; Sampson, Eric; Lee, Thomas C. M.
<x xml:space="preserve">Abstract</x> This article discusses the history and highlights of the Journal of Computational and Graphical Statistics (JCGS) as the journal approaches its 25th anniversary. A unique venture between three organizations—the American Statistical Association (ASA), the Institute of Mathematical Statistics (IMS), and the Interface Foundation of North America (IFNA)—JCGS has come to occupy an important niche in the statistical literature and establish itself as a forward‐thinking, high‐quality journal in its area. In addition to its contributions to the statistical literature, JCGS has often served as the test‐bed for new ideas and methods of publishing and delivery, each of which has presented challenges. But with every obstacle, the three partner organizations have risen to the occasion, supported the journal, and ensured that JCGS not only succeeds but thrives. We will take the reader through an undoubtedly incomplete, but hopefully informative history of JCGS from planning stages to inception and growth, with highlights and innovations presented along the way. The Supporting Information presents further details and data that could not fit within the space restrictions of the focus article itself. WIREs Comput Stat 2014, 6:233–239. doi: 10.1002/wics.1307 For further resources related to this article, please visit the WIREs website. Conflict of interest: The authors have declared no conflicts of interest for this article.